Disadvantages of the methodology and practice of analysis of the financial status of the enterprise: Causes, consequences, ways of elimination - V. Chubai; A. Zhyrnova (Economics, Entrepreneurship, Management, 2021)
Today, businesses operate in conditions of significant competition and a high level of unpredictability of changes in the environment. Therefore, for each company it is even more important to make optimal management decisions. A significant number of decisions are made based on the results of the analysis of the financial condition of the enterprise. However, the existing methodology and practice of financial analysis have many different shortcomings that significantly distort the results of the analysis. The main shortcomings can be divided into the following groups: organizational, methodological, technical, legislative, conceptual, informational. As a result of their presence, many users of financial information form incorrect conclusions and make suboptimal management decisions, which negatively affects the future results of the enterprise, related entities and the economy in general. Therefore, the purpose of scientific work is to study the shortcomings of the methodology and practice of financial analysis, and to find ways to address these shortcomings. The article examines foreign and domestic experience in analysing the financial condition of enterprises; identified and grouped the shortcomings of the methodology and practice of this type of analysis; the importance of taking into account the factors of its internal and external environments during the analysis of the financial condition of the enterprise is substantiated; recommendations for eliminating a number of shortcomings of the analysis of the financial condition of enterprises are offered. The results of the study will help to obtain much more reliable results of financial analysis, which will improve the quality of management decisions of operational, tactical and strategic nature